2014
DOI: 10.4321/s1578-84232014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Perfiles motivacionales de apoyo a la autonomía, autodeterminación, satisfacción, importancia de la educación física e intención de práctica física en tiempo libre

Abstract: Perfiles motivacionales de apoyo a la autonomía, autodeterminación, satisfacción, importancia de la educación física e intención de práctica física en tiempo libre Motivational profiles of autonomy support, self-determination, satisfaction, importance of physical education and intention to partake in leisure time physical activity Perfiles motivacionais de apoio à autonomia, auto-determinação, satisfação, importância da educação física e intenção de prática física no tempo livre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 32 publications
0
12
0
20
Order By: Relevance
“…That is why it is very important that the teacher directs the students through discipline strategies of concern and responsibility in order to achieve self-determined motivation [31,32]. In addition, the literature has shown that students who emphasise intrinsic reasons feel greater satisfaction in PE classes, improve their relationships with others, and value the subject more, attaching greater importance and usefulness to it [33,34]. Such a mindset favours a climate of learning in class.…”
Section: Introductionmentioning
confidence: 99%
“…That is why it is very important that the teacher directs the students through discipline strategies of concern and responsibility in order to achieve self-determined motivation [31,32]. In addition, the literature has shown that students who emphasise intrinsic reasons feel greater satisfaction in PE classes, improve their relationships with others, and value the subject more, attaching greater importance and usefulness to it [33,34]. Such a mindset favours a climate of learning in class.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to enjoyment, the study by Baena-Extremera et al [37], showed that this is an important antecedent for students' motivation towards the activities they carry out. Moreover, there is a positive and significant relationship between satisfaction in PE classes and the most self-determined motivation [6,38].…”
Section: Introductionmentioning
confidence: 98%
“…Those who have performed more physical activity at an early age demonstrate a tendency to continue sports throughout adulthood, unlike those who have led a more sedentary lifestyle [3]. Therefore, the important role played by physical activity is evident, and motivation in PE classes plays a decisive role in the concept, image and carrying out of physical activity outside of the school environment [4,5], for, as some authors indicate [6], the intention to carry out sports practices is related to satisfaction with PE classes.…”
Section: Introductionmentioning
confidence: 99%
“…Esta valoración del alumno sobre la importancia y utilidad de esta asignatura, ha sido ampliamente estudiada (Gómez-López, Ruiz-Juan, García-Montes, Baena-Extremera, y Granero-Gallegos, 2007; Granero-Gallegos, Baena-Extremera, Gómez-López, y Abraldes, 2014b; Granero-Gallegos, Baena-Extremera, Gómez-López, y Abraldes, 2014c; Moreno, Llamas, y Ruiz, 2006b;Moreno y Llamas, 2007), demostrando que es otro aspecto que influye en la adquisición de hábitos de práctica física. Diferentes estudios demostraron que los alumnos que presentaban una alta importancia y utilidad a la EF eran los que mayor actividad física extraescolar practicaban (Granero-Gallegos, Baena-Extremera, Pérez-Quero, Ortíz-Camacho, y Bracho-Amador, 2012;Granero-Gallegos et al, 2014a;Moreno-Murcia et al, 2013).…”
Section: Introductionunclassified